Ochrona praw autorskich w Internecie na podstawie dyrektywy Parlamentu Europejskiego i Rady (UE) 2019/790 - Włodarczyk, Julia (Wydawnictwo C.H. Beck, 2023)
The purpose of this paper is to present the possibilities of copyright protection through the mechanisms resulting from Directive (EU) No 2019/790. The article discusses issues related to, i.a. the institution of permitted use and the liability of the provider of online content sharing services and current legal issues related to them. The author also presents the problems connected with the implementation of Directive into Polish law and possible ways of protecting copyright through the use of appropriate mechanisms.
Keywords: Directive (EU) 2019/790; copyright; copyright protection; Internet; Digital Single Market; implementation; fair use; host provider